2014
DOI: 10.1002/pip.2536
|View full text |Cite
|
Sign up to set email alerts
|

Cu(In,Ga)Se2 superstrate solar cells: prospects and limitations

Abstract: Superstrate solar cells were prepared by thermal evaporation of Cu(In,Ga)Se2 onto ZnO coated glass substrates. For the first time, photo-conversion efficiencies above 11% were reached without the necessity of additional light soaking or forward biasing of the solar cell. This was achieved by modifying the deposition process as well as the sodium doping. Limitations of the superstrate device configuration and possible ways to overcome these were investigated by analyzing the hetero-interface with electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 35 publications
5
40
0
Order By: Relevance
“…It was shown before, that the presence of Na (and possibly F) during absorber formation significantly catalyzes the formation of Ga 2 O 3 at the TCO/chalcopyrite interface, which potentially leads to long‐ranging redistributions in Ga and In in the absorber . In order to investigate the effect of the Na supply method and the presence of Al 2 O 3 on the chemical and structural properties, the different samples on IOH thin were analyzed by STEM and EDS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown before, that the presence of Na (and possibly F) during absorber formation significantly catalyzes the formation of Ga 2 O 3 at the TCO/chalcopyrite interface, which potentially leads to long‐ranging redistributions in Ga and In in the absorber . In order to investigate the effect of the Na supply method and the presence of Al 2 O 3 on the chemical and structural properties, the different samples on IOH thin were analyzed by STEM and EDS.…”
Section: Resultsmentioning
confidence: 99%
“…An electrically unfavorable back contact junction after high temperature CIGS deposition ( T CIGS > 500°C) was determined as the main obstacle. A supposedly detrimental Ga 2 O 3 formation at the absorber/TCO interface (for AZO and ITO) or a reduced conductivity of FTO by a fluorine loss during high temperature absorber deposition was suggested as possible origin. On the other hand, Mollica et al have demonstrated ohmic behavior of FTO and AZO layers on CIGS (deposited at T CIGS > 500°C) and used these materials as appropriate TBCs in ultra‐thin CIGS devices .…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 6, the PL spectrum for a band gap graded CIGS absorber on Mo back contact is influenced by interferences which are not in phase with the measured 1 À R. The CIGS absorber was deposited by three-stage evaporation as described elsewhere, 19 giving a double band gap grading with the minimum, or notch, at around 300 nm from the absorber surface. Radiative recombination will be highest in this notch and the distribution of luminescence centres can be approximated by a Gaussian centred at this position.…”
Section: Wide Angle Interference In Notch Profile Cigsmentioning
confidence: 99%
“…In addition to metallic back contacts, we also studied MoO x and Cu 12 Sb 4 S 13 as charge-selective layers on Mo electrodes (Table II), similar to what has been previously studied for CdTe [41] and CIGS [42]. The PV devices (Table II).…”
Section: Optimization Of Back Contactmentioning
confidence: 99%